Conhecimentos e práticas de cirurgiões-dentistas sobre processamento de pontas polidoras: estudo transversal - Vargas, Renata de Paula (2021)
The aim of the study was to evaluate the practices of Brazilian dentists regarding the processing of resin restoration polishing tips after clinical use, as well as the perceived level of knowledge about biosafety standards regarding composite resin and instrumental polishing tips semi-critical; which is an indispensable understanding, regardless of the COVID-19 pandemic scenario, as the dental environment is prone to various contaminations by endless pathogenic microorganisms. Therefore, a cross-sectional study was developed through an online questionnaire consisting of 22 questions related to the profile of the dentist, the level of knowledge of biosafety and the practices of processing polishing tips. A total of 828 Brazilian dentists were included between November 2020 and January 2021. Descriptive and bivariate statistical analyzes were performed, using the Chi-Square Test (a = 0.05) for the outcome variables. Of the total respondents, 78.3% were women, 46.3% had less than 5 years of practice. Regarding clinical practice, 89% reported performing composite resin restorations and 95.4% consider it an important polishing step in the completion of composite resin restorations. However, 73.6% feel the lack of a cleaning protocol for the instruments that are used in the clinical routine for restoration. Furthermore, 86.4% of respondents are unable to discard polishing tips after a single use, and 64.3% indicate that regarding the reuse of tips, they could observe deleterious effects after submission to steam autoclave sterilization cycles. In this context, it is concluded that further study is needed to develop protocols for the proper processing of polishing tips, which is a complex cross-infection control associated with a reduction in damage to these tips.